Historical developments of atrial septal defect closure devices: what we learn from the past - Martina Nassif; Mohammad Abdelghani; Berto J. Bouma; Bart Straver; Nico A. Blom; Karel T. Koch; Jan G.P. Tijssen; Barbara J.M. Mulder; Robbert J. de Winter (2016)
Since King and Mills' pioneering work in percutaneous closure devices of secundum atrial septal defects (ASD) four decades ago, developments in device shape, material and implantation technique led to adoption of percutaneous ASD closure as current treatment of choice. Not only was the feasibility of such a percutaneous procedure tested altogether, but pursuing the ideal device in terms of safety and efficacy became priority.In this review we present the historical development of ASD devices in design, material and technique with clinical data, and provide the future perspectives in percutaneous ASD closures.An 'ideal device' requires complete defect closure with negligible risk of complications using a safe, straightforward delivery technique with repositioning and retrieving properties. Some of the devices currently at hand come close to fulfilling these criteria, however none seem to provide those prerequisites completely. By understanding how challenges in device development were overcome in the past, new insights into future improvements are given.